2023
DOI: 10.1101/2023.06.27.546055
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Whole-brain annotation and multi-connectome cell typing quantifies circuit stereotypy inDrosophila

Philipp Schlegel,
Yijie Yin,
Alexander S. Bates
et al.

Abstract: The fruit flyDrosophila melanogastercombines surprisingly sophisticated behaviour with a highly tractable nervous system. A large part of the fly's success as a model organism in modern neuroscience stems from the concentration of collaboratively generated molecular genetic and digital resources. As presented in our FlyWire companion paper1, this now includes the first full brain connectome of an adult animal. Here we report the systematic and hierarchical annotation of this ~130,000-neuron connectome includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
124
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(124 citation statements)
references
References 138 publications
(218 reference statements)
0
124
0
Order By: Relevance
“…Five identified KCγ-d's did not receive any inputs from VPNs or LVINs, and instead received input from olfactory PNs (Figure 5B). This median of 3 visual inputs per KCγ-d is slightly lower than the median 5-6 inputs received by olfactory Kenyon cells in general, and less than the 4-8 inputs that their closest developmental sisters, olfactory KCγ-main, receive in this brain 8,28,47 . We next analyzed the origin of inputs onto each cell (medulla, lobula, accessory medula or LVIN).…”
Section: Individual Kcγ-d's Select Inputs Randomly From a Precise Set...mentioning
confidence: 60%
See 3 more Smart Citations
“…Five identified KCγ-d's did not receive any inputs from VPNs or LVINs, and instead received input from olfactory PNs (Figure 5B). This median of 3 visual inputs per KCγ-d is slightly lower than the median 5-6 inputs received by olfactory Kenyon cells in general, and less than the 4-8 inputs that their closest developmental sisters, olfactory KCγ-main, receive in this brain 8,28,47 . We next analyzed the origin of inputs onto each cell (medulla, lobula, accessory medula or LVIN).…”
Section: Individual Kcγ-d's Select Inputs Randomly From a Precise Set...mentioning
confidence: 60%
“…Data and accompanying annotations from the FlyWire v630 snapshot were used 8,47,48,[88][89][90][91] . Our analyses used a ≥5 synapse threshold when determining a connection between neurons unless stated otherwise, in keeping consistent with connections indicated in Codex (https://codex.flywire.ai/).…”
Section: Identification and Characterization Of Direct Visual Inputs ...mentioning
confidence: 99%
See 2 more Smart Citations
“…In our scRNA-seq dataset, there are 188 distinct clusters, of which only 83 are annotated today. Recent efforts to map the fly brain through EM and connectomics studies have identified 4,552 morphological cell types (Schlegel et al, 2023). SRT can provide a bridge between scRNA-seq studies and morphology-based studies.…”
Section: Spatial Transcriptomics Allows the Localization Of Cell Type...mentioning
confidence: 99%